2004
DOI: 10.1021/la036414y
|View full text |Cite
|
Sign up to set email alerts
|

Iron Wheels on Silicon:  Wetting Behavior and Electronic Structure of Adsorbed Organostannoxane Clusters

Abstract: Atomic force microscopy and synchrotron radiation (SR) spectroscopy have been used to study the wetting behavior and electronic structure of thin films of a novel organometallic cluster--[BuSn(O)OC(O)Fc]6 ("Fc" = ferrocenyl)--on silicon substrates. This cluster comprises six ferrocene units connected to a stannoxane central core--"an iron wheel on a tin drum" (V. Chandrasekhar; et al. Angew. Chem., Int. Ed. 2000, 39, 1833). Thin films spin-cast onto native oxide-terminated silicon readily dewet the substrate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Concerning us here, due to their crystallographic statistical indistinguishability one cannot be sure that a given nanoparticle cellular network has formed through a nucleation and growth process as opposed to Bénard-Marangoni convection, but it is believed to be the process at play for the majority of experimentally observed cellular morphologies since Bénard-Marangoni convection only occurs within a narrow window of parameter space. Since these pattern formation mechanisms are primarily determined by properties of the solvent and the local environment, the resultant pattern morphologies can be observed for a range of solutes, including, for example, organometallic clusters [39] and collagen [40].…”
Section: Worm-like and Cellular Morphologiesmentioning
confidence: 99%
“…Concerning us here, due to their crystallographic statistical indistinguishability one cannot be sure that a given nanoparticle cellular network has formed through a nucleation and growth process as opposed to Bénard-Marangoni convection, but it is believed to be the process at play for the majority of experimentally observed cellular morphologies since Bénard-Marangoni convection only occurs within a narrow window of parameter space. Since these pattern formation mechanisms are primarily determined by properties of the solvent and the local environment, the resultant pattern morphologies can be observed for a range of solutes, including, for example, organometallic clusters [39] and collagen [40].…”
Section: Worm-like and Cellular Morphologiesmentioning
confidence: 99%
“…11 Not only are these multimetallic clusters aesthetically appealing, they also find applications in materials research as reported in the recent literature. 12 In spite of their enormous potential, only a few molecular clusters based on main group 9,11 and transition metal 10 anchoring ferrocenes have been reported so far, whereas their lanthanide counterparts remains completely unexplored. Hence, we were interested in synthesizing air stable multiferrocene assem- blies based on a lanthanide oxygen cluster core.…”
Section: Introductionmentioning
confidence: 99%
“…The compound was characterized by FT-IR, 1 H and 13 C NMR. It is further supported by absorbance spectra shows high-energy ligand-centred π-π * electronic transition and metal ligand charge transfer.…”
Section: Resultsmentioning
confidence: 99%
“…Organometallic polymers have been attracting considerable attention in recent years with a view to generating new materials with interesting electrochemical, electronic and magnetic properties [1,2]. In particular, the ferrocene appended stannoxane frameworks are interest due to electrochemically inertness and do not interfere with the electrochemical properties of the peripheral ferrocene moiety [3][4][5].…”
Section: Introductionmentioning
confidence: 99%